Coronavirus infections in children: from SARS and MERS to COVID-19, a narrative review of epidemiological and clinical features - Iannarella, Rosanna; Lattanzi, Claudia; Cannata, Giulia; Argentiero, Alberto; Neglia, Cosimo; Fainardi, Valentina; Pisi, Giovanna; Esposito, Susanna (Acta Biomedica Atenei Parmensis, 2020)
Emerging and re-emerging viruses represent an important challenge for global public health. In the 1960s, coronaviruses (CoVs) were recognized as disease agents in humans. In only two decades, three strains of CoVs have crossed species barriers rapidly emerging as human pathogens resulting in life-threatening disease with a pandemic potential: severe acute respiratory syndrome coronavirus (SARS-CoV) in 2002, Middle-East respiratory syndrome coronavirus (MERS-CoV) in 2012 and the recently emerged SARS-CoV-2. This narrative review aims to provide a comprehensive overview of epidemiological, pathogenic and clinical features, along with diagnosis and treatment, of the ongoing epidemic of new coronavirus disease 2019 (COVID-19) in the pediatric population in comparison to the first two previous deadly coronavirus outbreaks, SARS and MERS. Literature analysis showed that SARS-CoV, MERS-CoV and SARS-CoV-2 infections seem to affect children less commonly and less severely as compared with adults. Since children are usually asymptomatic, they are often not tested, leading to an underestimate of the true numbers infected. Most of the documented infections belong to family clusters, so the importance of children in transmitting the virus remains uncertain. Like in SARS and MERS infection, there is the possibility that children are not an important reservoir for novel CoVs and this may have important implications for school attendance. While waiting for an effective against SARS-CoV-2, further prevalence studies in paediatric age are needed, in order to clarify the role of children in different age groups in the spread of the infection.